Translating the Untranslated: Heterolingualism in F. G. Paci’s Black Madonna - Giuffredi, Ottavia (Université d'Ottawa / University of Ottawa, 2018)
The approach to translating multilingual texts has long been a subject of debate among scholars and translators, sparking discussions on which translational choices and strategies should be employed. An additional challenge occurs when a minority language in a multilingual (or rather, heterolingual) text becomes the target language. In these circumstances, the translator faces the dilemma of choosing how to preserve the Otherness that the non-dominant language conveys in the first text without overly manipulating it or stripping it of its nature. My analysis focuses on the challenges of translating Black Madonna (1982), a novel by prolific Italian-Canadian writer Frank Paci. Like many Italian-Canadian authors, the vast majority of Paci’s novels feature untranslated Italian terms and dialogues throughout the text. The first chapter of this thesis provides an introduction to the author and the basic concepts around which I structure my discourse, such as immigrant writing and the so-called ‘linguistic stones’ (untranslated terms). The section that follows features an overview of the most prominent Italian-Canadian plurilingual writers, as well as a brief analysis of a few selected works with a special focus on Scarpe Italiane (2007), the only novel by Paci to ever be translated into Italian. The research moves on to theories of translation, discussing various strategies and solutions proposed by scholars involved in the debate. The following chapter consists of a commentary in which I support a balance of foreignization and domestication by converting Italian terms into the appropriate regional dialect, since dialect is a prominent element in Paci’s novels. Finally, in the last section, I provide my translation of the novel into Italian.
Keywords: Heterolingualism; Multilingualism; Paci; Italian-Canadian; Minority; Otherness; Foreignization; Domestication